Reaksi kimia dalam bidang pertanian: pengaruh reaksi kimia tanah terhadap kesuburan tanaman - anggita, ardina davi (Maliki Interdisciplinary Journal, 2025)
Soil fertility is a major factor in the success of agricultural cultivation. One important aspect that influences soil fertility is the chemical reactions that occur within it and the availability of nutrients. Various reactions such as acid-base reactions (pH), cation exchange (CEC), reduction-oxidation (redox) reactions, and the process of dissolution and precipitation of nutrients that can be absorbed by plants. This article discusses the influence of various chemical reactions in the soil and the factors that can affect plant fertility. In addition, external influences of human activities also significantly impact the level of soil fertility, such as fertilization practices and irrigation management. This article examines how these chemical reactions can increase or inhibit the absorption of nutrients in the soil by plants. It is hoped that this article will provide a deeper understanding of the role of chemical reactions in the soil on plant fertility by examining various types of reactions and their impact on nutrient availability and biological activity in the soil, thereby helping to raise awareness of the importance of proper soil chemical management to maintain long-term soil productivity and health.